The pluralism of fairness ideals : an experimental approach - Erik Ø. Sørensen; Astri D. Hole; Alexander W. Cappelen; Bertil Tungodden (Center for Economic Studies and ifo Institute (CESifo), 2005)
A core question in the contemporary debate on distributive justice is how the fair distribution of income is affected by differences in talent and effort. Important theories of distributive justice, such as strict egalitarianism, liberal egalitarianism and libertarianism, all give different answers to this question. This paper presents the results from a version of the dictator game where the distribution phase is preceded by a production phase. Each player's contribution is a result of an exogenously given talent and a chosen effort. We estimate simultaneously the prevalence of three main principles of distributive justice among the players as well as the distribution of weights they attach to fairness considerations.
Keywords: D63; 330; Vermögensverteilung; Verteilungsgerechtigkeit; Verteilungstheorie; Qualifikation; Leistungsmotivation; Spieltheorie